1996
DOI: 10.1159/000189340
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Anti-HCV Antibody-Positive Patients with Hepatocellular Carcinoma on Chronic Hemodialysis: Recommendation of Periodic Ultrasonography for Early Detection

Abstract: We analyzed 10 patients (male:female 9:1, mean age 64.2 years) who developed hepatocelluar carcinoma during the observation period of 2 years among 2,164 chronic hemodialysis patients in 23 dialysis centers. Among them, 409 patients were positive for serum anti-HCV antibodies (19%). They were all positive for serum anti-HCV antibodies but negative for HBs antigen. None of the anti-HCV antibody-negative patients developed hepatocellular carcinoma during this period. Although liver function tests of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In the present study, the elevation of serum ALT above twice the normal range was observed in only 1 of 9 patients with chronic hepatitis C, and in some patients, serum aminotransferase levels were kept within the normal range despite histological findings of chronic active hepatitis. Recently, Sakai et al [23]reported that liver function tests were within the normal range in most patients with hepatocellular carcinoma associated with HCV infection in hemodialysis patients. Therefore, physicians should be careful not to miss liver cirrhosis or hepatocellular carcinoma in HCV carriers undergoing hemodialysis even if their serum aminotransferase levels are within the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the elevation of serum ALT above twice the normal range was observed in only 1 of 9 patients with chronic hepatitis C, and in some patients, serum aminotransferase levels were kept within the normal range despite histological findings of chronic active hepatitis. Recently, Sakai et al [23]reported that liver function tests were within the normal range in most patients with hepatocellular carcinoma associated with HCV infection in hemodialysis patients. Therefore, physicians should be careful not to miss liver cirrhosis or hepatocellular carcinoma in HCV carriers undergoing hemodialysis even if their serum aminotransferase levels are within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, histopathological examination is necessary in hemodialysis patients with chronic HCV infection even if their serum aminotransferase levels are kept within the normal range. Similarly, ultrasonography and/or computed tomography should be performed in these patients in order to detect small hepatocellular carcinoma [23]. From these results, IFN therapy should be indicated in hemodialysis patients before developing hepatocellular carcinoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study published in 1996 found that the frequency of HCV-positive HD patients was as high as 18.9% (409/2,164), while HCC was observed in only 2.4% (10/409) of HD patients with HCV infection (19). Factors associated with HCC in HCV-positive HD patients have remained elusive.…”
Section: Discussionmentioning
confidence: 96%